Analysis Of Patterns And Structure Of Use Of Space In Belawan Port Area And Surroundings - Sary, Sry Puspa; Nasution, Zulkifli; Lubis, Riadil Akhir (Budapest International Research and Critics University, 2021)
This study aims to analyze the use of spatial patterns and structures from policies that have been established through the Medan City Spatial Planning (RTRW) and the Medan Belawan District Spatial Detail Plan (RDTR) against current conditions. The analytical method used in this research is descriptive qualitative analysis. Qualitative descriptive analysis is a research method that gives a careful description of certain individuals or groups about the conditions and symptoms that occur. Qualitative descriptive methods were carried out to see the extent of space utilization, spatial descriptive analysis to see the distribution of land use which refers to predetermined spatial patterns and structures, and perspective analysis to determine research location development strategies from the researcher's point of view. The data analysis technique used in this study is GIS analysis using overlays, where this technique is used to determine the suitability of land use changes with land capabilities. From the results of this study, it can be conveyed that the implementation of development in Medan Belawan District refers to and is guided by spatial planning in the use of spatial patterns and spatial structures. Where in the embodiment of development which refers to the RDTR of Medan Belawan Sub-district is 81.90% appropriate, but for the embodiment of the spatial structure between the RDTR of Medan Belawan District with the actual condition of 35.43%.